Edoxaban Monotherapy in Nonvalvular Atrial Fibrillation Patients with Coronary Artery Disease. (17th December 2022) - Fukamachi, Daisuke; Okumura, Yasuo; Matsumoto, Naoya; Tachibana, Eizo; Oiwa, Koji; Ichikawa, Makoto; Haruta, Hironori; Nomoto, Kazumiki; Arima, Ken; Hirayama, Atsushi
Abstract : Background . Current guidelines recommend an oral anticoagulant (OAC) monotherapy in patients with nonvalvular atrial fibrillation (NVAF) and stable coronary artery disease (CAD) 1 year postpercutaneous coronary intervention (PCI). It might be possible to shorten the time for de-escalation from a dual therapy to monotherapy, but data regarding de-escalation to an edoxaban monotherapy are lacking. This study aimed to assess the clinical safety of an edoxaban monotherapy in patients with NVAF and stable CAD. Methods . A multicenter, prospective, randomized, open-label, and parallel group study was established to investigate the safety of an edoxaban monotherapy in patients with NVAF and stable CAD including over 6 months postimplantation of a third-generation DES and 1 year postimplantation of other stents (PRAEDO AF study). Between March 2018 and June 2020, 147 patients from 8 institutions in Japan were randomized to receive either an edoxaban monotherapy ( n = 74) or combination therapy (edoxaban plus clopidogrel, n = 73). The primary study endpoint was the composite incidence of major bleeding and clinically significant bleeding, defined according to the ISTH criteria. Results . Major or clinically significant bleeding occurred in 2 patients in the monotherapy group (1.67% per patient-year) and in 5 patients in the combination therapy group (4.28% per patient-year) (hazard ratio, 0.39; 95% confidence interval, 0.08–2.02). There was no incidence of a myocardial infarction, stent thrombosis, unstable angina requiring revascularization, ischemic stroke, systemic stroke, or hemorrhagic stroke in either of the groups. Conclusions . The edoxaban monotherapy was shown to have acceptable clinical safety in patients with NVAF and stable CAD. The study was registered with the Japan Registry of Clinical Trials (jRCTs031180119 ).